Evidence that Evidence Doesn't Matter: The Case of Human Trafficking in Canada - Roots, Katrin; De Shalit, Ann (Atlantis)

(untitled) (Mount Saint Vincent University, 2015)
This article considers the ways in which the political pressures that have structured Canada’s involvement in the fight against human trafficking and the on-the-ground enforcement of laws adopted through Canada’s positioning as an anti-trafficking nation have created a problem that necessitates regulation. Although the problem could be interpreted as a legal fiction, its effects are real and include greater restrictions on migrants, a lack of attention to wide-ranging labour abuses, and the tightening of the net around sex work.